Análise do value relevance das informações financeiras dos fundos de investimentos imobiliários no Brasil - Silva, Thatiane de Oliveira da (2024)
This study investigated the influence of financial information on profits and net assets on the returns of Brazilian real estate funds, covering the period from January 2017 to December 2023. The hypothesis formulated was whether there is value relevance in financial information on profits (financial and accounting) and net assets in the returns of REITs (H1). By adopting fixed effects as the most appropriate strategy for analysis, the central variables (PLCC, PLFC, LLFC, and LLCC) showed low correlation with fund returns, suggesting that their fluctuations may not have a significant impact on shares in general. However, preliminary results indicate that in the fixed-effects model, there is a lack of direct influence of net assets and profits on fund returns. Thus, hypothesis H1 was not confirmed. These findings point to the complexity of the real estate fund market, suggesting that traditional accounting metrics may not be the only information in analyzing performance. These conclusions highlight the need for further studies to understand which information and macroeconomic data are truly relevant to real estate fund returns. Additionally, there is a suggestion to explore the Efficient Markets Theory, given that financial information may be relevant in specific markets that are still unclear for REITs.